2016
DOI: 10.1371/journal.pone.0145811
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Index Associates with Relative Sarcopenia and GH/ IGF- 1 Status in Obese Subjects

Abstract: IntroductionRecently the association between hepatic steatosis and sarcopenia has been described. GH/IGF-1 axis has been postulated to play a role in linking fatty liver and low muscle mass. The aim of our study was to explore the association between fatty liver index, sarcopenic obesity, insulin sensitivity, and GH/IGF-1 status.Methods427 subjects [age: 45.65±13.94 years, BMI: 36.92±6.43 kg/m2] were enrolled. Participants were divided into three groups: fatty liver index (FLI) <20, 20≥FLI<60, and FLI≥60. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…VAT is a metabolically-active endocrine organ that is associated with circulating biomarkers, such as triglycerides, HDL cholesterol, and GGT [2,3]. The VAI and FLI also correlate with insulin resistance, which is often observed among adults with excess VAT [4,7], and is a risk factor for cardiovascular disease and cancer [10]. Therefore metrics such as the VAI or FLI which simultaneously integrate measures of VAT quantity (i.e., VAT volume or area) and quality (i.e., VAT metabolic activity) may be an important first step to globally characterize VAT dysfunction and help to differentiate patients with metabolically healthy obesity versus patients with metabolically unhealthy obesity [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VAT is a metabolically-active endocrine organ that is associated with circulating biomarkers, such as triglycerides, HDL cholesterol, and GGT [2,3]. The VAI and FLI also correlate with insulin resistance, which is often observed among adults with excess VAT [4,7], and is a risk factor for cardiovascular disease and cancer [10]. Therefore metrics such as the VAI or FLI which simultaneously integrate measures of VAT quantity (i.e., VAT volume or area) and quality (i.e., VAT metabolic activity) may be an important first step to globally characterize VAT dysfunction and help to differentiate patients with metabolically healthy obesity versus patients with metabolically unhealthy obesity [11].…”
Section: Discussionmentioning
confidence: 99%
“…The FLI ranges from 0–100, with higher values indicating a greater likelihood of having hepatic steatosis [5]. The FLI is associated with abdominal fat mass ( r =0.662; P <0.001) and insulin sensitivity ( r =−0.335; P <0.001) in obese adults in the general population [7]. …”
Section: Methodsmentioning
confidence: 99%
“…An additional factor associated with sarcopenic obesity and potentially useful in the overall assessment of NASH patients is gamma-glutamyl tranferase level (GGT) [53], as elevated GGT levels were associated with increased risk of sarcopenia and sarcopenic obesity in a cohort of patients older than 50 years. Growth hormone (GH) and insulin- like growth factor 1 (IGF- 1) were also associated with increased risk of sarcopenic obesity and hepatic fat deposition [54]. …”
Section: Nutrition Assessment In Specific Etiologies Of Liver Diseasementioning
confidence: 99%
“…Several studies have shown that GH secretion is compromised in obese people, and GH and IGF-1 have been found to be involved in fatty infiltration of the liver [21]. On the other hand, the ectopic deposition of fat seems to be associated with reduced GH levels, as well as the decreased ability to produce GH with aging, which is one of the causes of body changes leading to excess adiposity and sarcopenia [22].…”
Section: Gh/igf-1 and Sarcopeniamentioning
confidence: 99%